Retrospective study of canine lymphoma in period 1990 - 2004, north region the of Paraná - Moreno, Kleber; Bracarense, Ana Paula Frederico Rodrigues Loureiro (Brazilian Journal of Veterinary Research and Animal Science, 2007)
Canine malignant lymphoma (CML) is a common lymphoid tumor. Canine lymphomas from 1990 to 2004 (n=186) were analyzed on epidemiological aspects. The occurrence of CML in males ( 58,6%) was greater than in females (41,4%). The middle age of affected dogs was 5,9 years. The most common breeds in this study were mixed breed (40,3%), German Sheepdog (8,6%), Rottweiler (8,1%) and Boxer (7,0%). For the anatomical classification and the clinical staging of CML, the most common were multicentric form (68,8%) and stage III (37,1%) and IV (43,5%), respectively.